Population-level gut microbiome and its associations with environmental factors and metabolic disorders in Southwest China - Qianyu Qu; Qingyu Dou; Zhejun Xiang; Bin Yu; Lili Chen; Zhenxin Fan; Xing Zhao; Shujuan Yang; Peibin Zeng (npj Biofilms and Microbiomes)
Abstract Gut microbiota affects host health and disease. Large-scale cohorts have explored the interactions between the microbiota, host, and environment to reveal the disease-associated microbiota variation. A population-level gut metagenomic cohort is still rare in China. Here, we performed metagenomic sequencing on fecal samples from the CMEC Microbiome Project in Southwest China. In this study, we identified host socioeconomics, diet, lifestyle, and medical measurements that were significantly associated with microbiome function and composition. We revealed extensive novel associations between the host microbiome and common metabolic disorders. Our results provide new insight into associations of gut microbiota with metabolic disorders so as to support the translation of gut microbiome findings into potential clinical practice.